2003
DOI: 10.1002/cbic.200300617
|View full text |Cite
|
Sign up to set email alerts
|

A New Furoxan NO‐Donor Rabeprazole Derivative and Related Compounds

Abstract: Stomach pump: Gastric antisecretory and protective activity against damaging agents are shown by the pump inhibitor rabeprazole (1). This compound is also potently active against Helicobacter pylori strains that are resistant to metronidazole. Modification of 1 with a furazan or furoxan group significantly reduced its antisecretory potency but not its efficacy. The furoxan analogue, which can act as an NO donor, has a protective activity comparable to that of the parent molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…All these NO donor hybrids were reviewed [2,17]. More recently, NO donor furoxans were also joined to 1,4-dihydropyridine Ca 2+ -channel activators [18], as well as to the REC15/2739, a uroselective α 1 -antagonist [19], and to the rabeprazole, a potent inhibitor of H + /K + -ATPase enzyme [20]. One of the problems that must be addressed when working with hybrid drugs is their balance.…”
Section: Furoxan/drug Hybridsmentioning
confidence: 99%
“…All these NO donor hybrids were reviewed [2,17]. More recently, NO donor furoxans were also joined to 1,4-dihydropyridine Ca 2+ -channel activators [18], as well as to the REC15/2739, a uroselective α 1 -antagonist [19], and to the rabeprazole, a potent inhibitor of H + /K + -ATPase enzyme [20]. One of the problems that must be addressed when working with hybrid drugs is their balance.…”
Section: Furoxan/drug Hybridsmentioning
confidence: 99%
“…Gasco first reported the thiol mediated release of NO from furoxan ( 2 ) and the resulting vasodilatory properties in 1994 27. Since that time, the core oxadiazole-2-oxide moiety has been conjugated to numerous bioactive compounds in attempts to make chimeric small molecules with dual activities including NO-donating β–adrenoceptor agonists,28 NO-donating aspirin conjugates29 and NO-donating proton pump inhibitors 30…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Treger et al [ 32 ] reported that oxadiazole-2-oxides kill Ancylostoma ceylanicum and proved that their target was not glutathione reductase. Besides these reasons, several studies [ 33 36 ] have shown that oxadiazole-2-oxides have many functions, which have been used in new drug developments against bacteria, fungi, viruses, worms, tumors, syncopes and immune suppressors. This indicates that oxadiazole-2-oxides may have a lot of function targets.…”
Section: Discussionmentioning
confidence: 99%